2017
DOI: 10.1016/j.ejbas.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of osmotic stress on seedling growth observations, membrane characteristics and antioxidant defense system of different wheat genotypes

Abstract: View related articles View Crossmark data Citing articles: 2 View citing articles Full Length Article Impact of osmotic stress on seedling growth observations, membrane characteristics and antioxidant defense system of different wheat genotypes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…Because the radicle grows to be in direct contact with the culture medium, water is absorbed from the culture medium and then the plumule supplies it to the rest of the plant (Cavallaroa et al, 2016;Laghmouchi et al, 2017). Accordingly, PL and RL provide an important instance whereby plants can be studied in how they respond to environmental stress (Mickky and Aldesuquy, 2017). The strongest possibility to grow in arid and saline areas occurs for plants that can maintain a longer plumule and radicle when exposed to stress conditions (Goatley et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Because the radicle grows to be in direct contact with the culture medium, water is absorbed from the culture medium and then the plumule supplies it to the rest of the plant (Cavallaroa et al, 2016;Laghmouchi et al, 2017). Accordingly, PL and RL provide an important instance whereby plants can be studied in how they respond to environmental stress (Mickky and Aldesuquy, 2017). The strongest possibility to grow in arid and saline areas occurs for plants that can maintain a longer plumule and radicle when exposed to stress conditions (Goatley et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Under drought stress (Bani Seuf 7, Shandaweel 1 and Sakha 95) were tolerant genotypes, (Misr 2, Sohag 4 and Misr 1) were moderate genotypes, while (Giza 168, Misr 3 and Sids 12) were sensitive genotypes. In this regard, (Mickky et al 2017) studied some morphological traits on wheat seedlings after exposing wheat seedlings to PEG treatments and Sids 13 seemed to be the most tolerant variety followed by Masr 1, Masr 2, Gimmaza 9, Gimmaza 11, Sids 12, Sakha 93, Sakha 94, and Giza 186 and finally came Shandawel 1 with the maximum sensitivity. On the other hand, our results showed that under salinity stress, the tolerant genotypes included (Misr 2, Bani Seuf 7 and Sohag 4), the moderate genotypes included (Shandaweel 1and Sakha 95), and the sensitive genotypes included (Sids 12, Giza 168, Misr 1 and Misr 3).…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the research presented here was to investigate adaptation to osmotic stress at germination in diverse landraces of chiles collected from different cultivation regimes and ecozones within southern Mexico. We used polyethylene-glycol (PEG) to induce osmotic stress at the seed stage, as has been done in germination studies of other cultivated and wild species [32][33][34][35][36][37][38][39][40]. In most prior studies, PEG solutions were used to identify cultivars which perform well under both stress and un-stressed conditions, whereas here we aimed to identify G×E interactions among populations as an indication of local adaptation to drought stress.…”
Section: Introductionmentioning
confidence: 99%